Criticizing photographs : an introduction to understanding images - Barrett, Terry , 1945- (McGraw Hill, 2012)
Designed to help both beginning and advanced students of photography better develop and articulate thoughtful criticism. Organized around the major activities of criticism (describing, interpreting, evaluating, and theorizing), this title provides a clear framework and vocabulary for students' critical skill development